2018
DOI: 10.1039/c7cy01861d
|View full text |Cite
|
Sign up to set email alerts
|

Role of lattice oxygen and oxygen vacancy sites in platinum group metal catalysts supported on Sr3Fe2O7−δ for NO-selective reduction

Abstract: The lattice oxygen in PGM/Sr3Fe2O7−δ contributes to the oxidation of CO and C3H6 and the oxygen vacancy sites can play a role in NO reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…[21][22][23] The oxygen vacancy formation energy, Evac, of perovskites is a multi-purpose descriptor that is extensively used for estimating the stability of compounds and their applicationspecific behaviors. 6,22,24,25 In recent studies, Evac is used as a performance descriptor for highly diverse chemical reactions including, carbon dioxide reduction 3,26,27 , hydrogen evolution 6,28,29 , nitrous oxide reduction 6,30 , volatile organic compound oxidation 3,6 , oxygen reduction 3,6,29,31,32 , and in addition to all these, for oxygen ion diffusion through materials. 24,33 The catalytic behavior and oxygen permeation performance of perovskites are influenced by the presence of oxygen atom vacancies in their structures.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…[21][22][23] The oxygen vacancy formation energy, Evac, of perovskites is a multi-purpose descriptor that is extensively used for estimating the stability of compounds and their applicationspecific behaviors. 6,22,24,25 In recent studies, Evac is used as a performance descriptor for highly diverse chemical reactions including, carbon dioxide reduction 3,26,27 , hydrogen evolution 6,28,29 , nitrous oxide reduction 6,30 , volatile organic compound oxidation 3,6 , oxygen reduction 3,6,29,31,32 , and in addition to all these, for oxygen ion diffusion through materials. 24,33 The catalytic behavior and oxygen permeation performance of perovskites are influenced by the presence of oxygen atom vacancies in their structures.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…[21][22][23] The oxygen vacancy formation energy, Evac, of perovskites is a multi-purpose 4 descriptor that is extensively used for estimating the stability of compounds and their applicationspecific behaviors. 6,22,24,25 In recent studies, Evac is used as a performance descriptor for highly diverse chemical reactions including, carbon dioxide reduction 3,26,27 , hydrogen evolution 6,28,29 , nitrous oxide reduction 6,30 , volatile organic compound oxidation 3,6 , oxygen reduction 3,6,29,31,32 , and in addition to all these, for oxygen ion diffusion through materials. 24,33 The catalytic behavior and oxygen permeation performance of perovskites are influenced by the presence of oxygen atom vacancies in their structures.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…For example, Kang et al reported a Ni–Cu alloy supported on the Mg–Al mixed metal oxide, and the Ni 0.3 Cu 0.2 /2MgO·1/2MgAl 2 O 4 catalyst showed high catalytic activity, especially for HC oxidation in a reducing atmosphere . In addition, our group reported the application of perovskite-based metal oxides such as Sr 3 Fe 2 O 7−δ with topotactic properties for use as automobile exhaust catalysts. In these examples, lattice oxygen plays an active role in the reduction of NO and the oxidation of HCs and CO via the so-called Mars–van Krevelen mechanism. Thus, metal oxides, single metal sites, and metallic catalysts might also function via a similar mechanism at their surfaces.…”
Section: Introductionmentioning
confidence: 99%